Small Actions Big Changes: Can Director Rogayah Hang On? (Global Business Management Review (GBMR), 2022)
To run a business, whether it is manufacturing or service sector, the principles and process of managing the business leaders has to apply is almost similar. The business leadership has to organise all available resources towards effective planning, organising, and controlling for growth and development of business. A case study was organised to understand the branding and rebranding of a hotel in Malaysia. The study followed strictly the qualitative research method. The case study was conducted to provide valuable insight into in fundamentals of hotel management, management, fundamental of marketing, entrepreneurship and strategic management in its relevance in the hotel industry. This case study will focus on leadership issues and re-branding. However, the observations really pointed out into operational and strategic issues of a business organisation.